2003
DOI: 10.1074/jbc.m300730200
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Mechanisms of Nucleocytoplasmic Trafficking of Steroid Receptor Coactivator-1

Abstract: Steroid hormone receptors are ligand-stimulated transcription factors that modulate gene transcription by recruiting coregulators to gene promoters. Subcellular localization and dynamic movements of transcription factors have been shown to be one of the major means of regulating their transcriptional activity. In the present report we describe the subcellular localization and the dynamics of intracellular trafficking of steroid receptor coactivator 1 (SRC-1). After its synthesis in the cytoplasm, SRC-1 is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 80 publications
2
32
0
Order By: Relevance
“…In contrast, exogenously expressed GFPSRC-2 and GFPSRC-3 were localized exclusively in the nucleus, both diffusely and in discrete round granules. Our observation of SRC-1 localization is consistent with the presence of exogenously expressed SRC-1 detected by immuno-fluorescence in both cytoplasm and nucleus as speckles in all cell types [32]. Localization of transcriptional regulators in nuclear speckles has been described before, but the presence of similar structures in the cytoplasm is rarely observed [33,37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, exogenously expressed GFPSRC-2 and GFPSRC-3 were localized exclusively in the nucleus, both diffusely and in discrete round granules. Our observation of SRC-1 localization is consistent with the presence of exogenously expressed SRC-1 detected by immuno-fluorescence in both cytoplasm and nucleus as speckles in all cell types [32]. Localization of transcriptional regulators in nuclear speckles has been described before, but the presence of similar structures in the cytoplasm is rarely observed [33,37].…”
Section: Discussionsupporting
confidence: 91%
“…SRC-1 has been reported to be present in the nucleus [28,29,30], in the cytoplasm [31] or in both compartments [32]. Similar divergent data have been described for SRC-3, ranging from cytoplasmic to diffuse nucleoplasmic or discrete intranuclear foci [33,34].…”
Section: Discussionmentioning
confidence: 66%
“…The explanation for this opposite effect and the role of heterodimerization is still ambiguous, and the differences in transfection conditions, cell types, reporters, or promoters must be taken into consideration. Transcriptional cofactors are also another very important player to consider when evaluating the transcription activities of the GR and MR (Amazit et al, 2003), which were not discussed in the previous studies reporting heterodimer of GR and MR.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that steroid receptors interact with Crm1 thanks to a co-regulator behaving as an adapter. In this context, it has been recently reported that steroid receptor co-activator-1 (a member of the p160 family) is exported from cell nuclei by a LMB-sensitive process (Amazit et al 2003).…”
Section: Discussionmentioning
confidence: 99%